2017
DOI: 10.1039/c7mb00336f
|View full text |Cite
|
Sign up to set email alerts
|

HIV/HAART-associated oxidative stress is detectable by metabonomics

Abstract: Chronic human immunodeficiency virus (HIV) infection, separately and in combination with highly active antiretroviral therapy (HAART) is closely associated with oxidative stress (OS). Most studies demonstrating redox imbalances in HIV-infected individuals have done so using conventional biochemical methodologies. The limited simultaneous detection of multiple OS markers within one sample is a major drawback of these methodologies and can be addressed through the use of metabonomics. HIV-metabonomic studies uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(28 citation statements)
references
References 115 publications
1
27
0
Order By: Relevance
“…Also, specific ceramides are increased in PLHIV and are known to track 4-hydroxynonenal (4-HNE) [17]. Higher levels of methionine sulfone and ceramides are indicators of increased oxidative stress, which was observed in earlier studies [5]. A recent study from the Netherlands that analyzed targeted metabolites of biogenic amine, lipids, oxylipins, and oxidative stress showed minimal change after one year of ART [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, specific ceramides are increased in PLHIV and are known to track 4-hydroxynonenal (4-HNE) [17]. Higher levels of methionine sulfone and ceramides are indicators of increased oxidative stress, which was observed in earlier studies [5]. A recent study from the Netherlands that analyzed targeted metabolites of biogenic amine, lipids, oxylipins, and oxidative stress showed minimal change after one year of ART [10].…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic side effects of the ARV drugs mainly on the lipid profile has been extensively studied [3,4]. Previous studies showed that metabolic abnormalities are common in PLHIV both in untreated and treated conditions (reviewed in Reference [5]). Factors like host immune response, opportunistic infections, ART drugs, and HIV itself could be responsible for the metabolic derangement during HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, the cellular and molecular mechanism for this unequal response remains elusive. Although efficient at controlling viral load and restoring immune function, HIV antiretroviral therapies, especially the protease and reverse transcriptase inhibitors, have been shown to induce oxidative stress [50,140]. Interestingly, a long time treatment (more than 2 years) with antiretroviral therapy improves selenium levels as compared with HIV-infected patients not receiving the treatment [141].…”
Section: Selenium Selenoproteins and Viral Replicationmentioning
confidence: 99%
“…Besides inhibiting mtDNA replication, NRTIs can also directly damage mitochondrial enzymes, enhancing the generation of ROS production [127]. Indeed, an increase in oxidative stress has been frequently associated with antiretroviral treatment in HIV patients [128-130]. Several studies have demonstrated that the increase in ROS production mediated by HAART favours the onset of ageing-associated diseases [131-133].…”
Section: Art and Mitochondriamentioning
confidence: 99%